The Witch's Flight : The Cinematic, the Black Femme, and the Image of Common Sense - Keeling, Kara, 1971- (Book collections on Project MUSE., 2007)
Kara Keeling contends that cinema and cinematic processes had a profound significance for twentieth-century anti-capitalist Black liberation movements based in the United States. Drawing on Gilles Deleuze's notion of "the cinematic"--Not just as a phenomenon confined to moving-image media such as film and television but as a set of processes involved in the production and reproduction of social reality itself--Keeling describes how the cinematic structures racism, homophobia, and misogyny, and, in the process, denies viewers access to certain images and ways of knowing. She theorizes the Black femme as a figure who, even when not explicitly represented within hegemonic cinematic formulations of raced and gendered subjectivities, nonetheless haunts those representations, threatening to disrupt them by making alternative social arrangements visible.